Otomasi Sistem Hidroponik DFT (Deep Flow Technique) Berbasis Arduino Android dengan Memanfaatkan Panel Surya sebagai Energi Alternatif - Suprayitno MT, Eko Agus; M.Kom, Rohman Dijaya; ST, M. Atho'illah (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2018)
The application of hydroponic farming methods has been widely applied by the community, the system used is still manual so that it lacks quality, both in terms of humidity and growth. For that we need a system that is able to regulate the time of watering and the provision of nutritional solutions automatically without disturbing the activity. In the design of an automatic DFT hydroponic system using an Android Arduino based solar panel. Where the solar panel system functions as a renewable energy substitute for PLN which will fill the accumulator. The accumulator filling process is equipped with a solar charge controller module, which aims to avoid overcharging the accumulator. The process of watering and administering nutritional solutions is controlled by the Arduino UNO microcontroller which is integrated with the DS1307 RTC module, the HC-05 bluetooth serial communication module and the android smartphone application as the relay module to turn on and turn off the circulation pump according to a predetermined schedule. Test results and tool performance are in accordance with the plan, namely the efficiency of the use of solar panels. This is indicated by scheduling the circulation of the circulating pump for 1 hour from the estimated calculation of the maximum pump speed for 2.38 hours. In testing the transmission of data from bluetooth HC-05 connected to a bluetooth smartphone with unhindered conditions obtained a maximum distance of 15 meters and with a concrete wall obstruction a maximum distance of 5 meters, with plywood walls a maximum distance of 8 meters.